Kesadaran Masyarakat Terhadap Kebijakan Hukum Perlindungan Data Pribadi Di Era Digital Di Kota Kendari Sulawesi Tenggara - Muhammad Jafar, Andi; Lanontji, Muryanto; Fahmi, Arif (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2025)
This study addresses public awareness of the legal provisions regarding the protection of personal data in the digital age, highlighting public understanding and attitudes towards applicable regulations in Kendari City, Southeast Sulawesi. The research employs a qualitative approach with empirical-normative methods, combining normative analysis of regulations and policies related to personal data protection with empirical testing of their implementation and social impact in society. The study reveals that although the public has a high awareness of the importance of maintaining personal data, only 40% of respondents are aware of Law No. 27 of 2022 on Personal Data Protection. The majority of the public lacks an understanding of legal concepts such as data controllers and data processing procedures. This shows a significant gap between legal awareness and understanding, which has the potential to undermine the effectiveness of implementing data protection policies. The findings indicate the need for more comprehensive education and stronger law enforcement to build public trust in digital data protection systems.